2018
DOI: 10.1007/s10072-018-3339-9
|View full text |Cite
|
Sign up to set email alerts
|

Neurology and the Internet: a review

Abstract: Nowadays, the Internet is the major source to obtain information about diseases and their treatments. The Internet is gaining relevance in the neurological setting, considering the possibility of timely social interaction, contributing to general public awareness on otherwise less-well-known neurological conditions, promoting health equity and improving the health-related coping. Neurological patients can easily find several online opportunities for peer interactions and learning. On the other hand, neurologis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 73 publications
1
31
0
Order By: Relevance
“…The most frequent reasons for using social media were to obtain health information, maintain contact within the medical community, provide information to colleagues and patients, and receive clinical updates. These findings emphasize the wide range of opportunities provided to physicians by social media and are consistent with the results of a systematic review that identified the following seven main uses of social media platforms for health communication: (1) providing health information on a range of conditions; (2) providing answers to medical questions; (3) facilitating dialogue between patients to patients, and patients and health professionals; (4) collecting data on patient experiences and opinions; (5) use for health intervention, health promotion, and health education; (6) reducing stigma; and (7) providing online consultations (4).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The most frequent reasons for using social media were to obtain health information, maintain contact within the medical community, provide information to colleagues and patients, and receive clinical updates. These findings emphasize the wide range of opportunities provided to physicians by social media and are consistent with the results of a systematic review that identified the following seven main uses of social media platforms for health communication: (1) providing health information on a range of conditions; (2) providing answers to medical questions; (3) facilitating dialogue between patients to patients, and patients and health professionals; (4) collecting data on patient experiences and opinions; (5) use for health intervention, health promotion, and health education; (6) reducing stigma; and (7) providing online consultations (4).…”
Section: Discussionsupporting
confidence: 86%
“…The use of digital devices and the introduction of online social networks have transformed many aspects of clinical practice. Both patients and physicians are increasingly using the Internet and social media platforms to obtain, provide, share, and comment on health information (1,2). On social media, users can create and share content and can take part in social networking collaborative projects (e.g., Wikipedia), content communities (e.g., YouTube), social networks (e.g., Facebook), web logs (blogs), or virtual games (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that online interest in borreliosis and in West Nile virus disease correlates with their prevalence [7]. Most studies of neurological diseases did not show a correlation of web visitors' interest with the disease prevalence [3,8].…”
Section: Discussionmentioning
confidence: 99%
“…6 Reporting prevalence of social networking site use among parents of preterm infants. 7 Determining parents perception and preferences for information sharing in the neonatal intensive care unit.…”
Section: Evaluation Of Social Media Usementioning
confidence: 99%
“…The use of social media in healthcare for increasing speed of communication, distributing accurate information, and promoting knowledge of support, treatments and self-care options is becoming more widespread [6,7]. Patient-and family-centered healthcare, which acknowledges that patients and their informal caregivers are central figures in decision-making and delivery of care [8], recognizes that patients and caregivers exist within an online social structure and network of relationships [9].…”
Section: Introductionmentioning
confidence: 99%